Assessment of the distribution profile of light non-aqueous phase liquid in unsaturated zone under the influence of rainfall recharge - Kamaruddin, Samira Albati (2012)
Leaking from underground storage and surface spills of hydrocarbon sources can cause serious light non-aqueous phase liquid (LNAPL) contamination in subsurface environments. In real conditions, the multiphase flow during LNAPL migration can be affected by rainfall recharge. To consider this, a study was carried out to investigate the distribution of LNAPL migration in the unsaturated zone through qualitative and quantitative experiments, as well as numerical simulations. Both qualitative and quantitative experiments utilized light reflection method (LRM) for NAPL saturation imaging technique. In the qualitative experiment, the image analysis used conventional calibration relationship to determine the distribution profile of LNAPL in a 2-D model. The penetration depth of benzene and toluene after 24 h of injection initiated was 37.0 cm and 33.4 cm, respectively. At the same time, the toluene plume occupied larger area (30.7%) compared to benzene plume (25.2%). The benzene moved deeper as expected due to the lower retardation factor, R and higher water solubility compared to toluene. More benzene was volatilized because its vapor pressure is higher than toluene. The differences showed that the chemical properties of the LNAPL source have considerable influence on their transport mechanism through porous media. Rainfall recharge showed minimal effects to benzene and toluene distribution due to its volatilization mechanism in porous media. In the quantitative experiment, multispectral imaging technique was applied to develop reliable image analysis. The average optical density (OD) from the captured images of samples containing twofluid phase and three-fluid phase systems were analyzed to obtain the water and LNAPL saturation (Sw and So). The R2 results vary from 0.766 to 0.986 for the average OD and fluid saturation linear relationship. The distribution assessment of the LNAPL (isoparaffin liquid) showed that it was easily mobilized downward by the rainfall recharge. The recharge significantly reduced the LNAPL saturation at the upper part of capillary interface. At the lower interface, lens of LNAPL was observed to form higher So and tends to flow horizontally towards the water wells. This evaluation showed that rainfall recharge has significant effect on the LNAPL distribution. The LNAPL spill containing benzene, which has similar properties to the one tested in the qualitative experiment was simulated using the MOFAT program. Simulations were performed for three different spill sites in a 2-D model domain. The results showed that different locations of spill site produced different shapes and levels of oil saturation contours. The predicted maximum oil saturation for the edge spillage and center spillage were 0.38 and 0.43, respectively. The distribution of oil saturation during LNAPL redistribution was influenced by the direction of the slope of water table. The spill that occurred at the upper stream tends to create LNAPL lens along the groundwater surface if the higher LNAPL content was capable to move deeper reaching the groundwater level. Generally, 1 m3 of oil spill containing 10.5% of benzene resulted in water and gas concentration ranging up to 183 g m-3 and 43 g m-3, respectively. The distribution of concentration of water- and gas-phase was largely influenced by the direction of groundwater flow towards the lower water gradient.